Amalan Sholat Hifdzil Qur’an : Kajian Living Qur’an Di Pptq Al-Hidayah Tulungagung - Firlana, Amalia Rizky (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2019)
This paper explains the phenomenon of the Koran of life. The study of the practice of the verses of the Koran in daily life so as to give rise to certain meanings for its practitioners is proof that the Koran can take the form of anything other than text. The object of research in this study is the interpretation of the Hifdzil Qur’an prayer which is located in Ponpes Tahfidz Al-Qur’an Al-Hidayah Tulungagung with a phenomenological approach and observation-interview method with purposive sampling technique. This research resulted in the transmission of the continuity of sanad with PP Putri Al-Fattah Mangunsari, and the transformation of differences in how to perform the hifdzil Qur’an prayer. Social construction that occurs in the practice of the hifdzil Qur’an prayers in PPTQ Al-hidayah is divided into 3; (1) externalization: the practice of the hifdzil Qur’an prayer is made a mandatory regulation by caregivers and caretakers; (2) objectivation: the practitioner feels accustomed because of the intensity, and; (3) internalization: practitioners understand the meaning and feel the effects after performing the hifdzil Qur’an prayer.